Effect of gamma radiation on Phenoloxidase pathway, antioxidant defense mechanism in Helicoverpa armigera (Lepidoptera: Noctuidae) and its implication in inherited sterility towards pest suppression. (January 2014) - Sachdev, Bindiya; Zarin, Mahtab; Khan, Zubeda; Malhotra, Pawan; Seth, Rakesh Kumar; Bhatnagar, Raj K.
Abstract Purpose: To investigate age-correlated radiosensitivity in highly radioresistant lepidopteran pest, Helicoverpa armigera, upon exposure to ionizing radiation and to examine the irradiation impact on stress-molecular responses in F1 (first-filial) progeny of irradiated (100 Gy) male moths in relation to its reproductive behavior. Materials and methods: Efficacy of sub-lethal gamma radiation was evaluated on two markedly apart ontogenic stages, neonates and adult moths. Differential growth, reproductive behavior and stress-indicating molecular responses were examined upto F1 progeny of sub-sterilized moths. Free-radical scavenging enzymes, superoxide dismutase (SOD), catalase (CAT) and Phenoloxidase cascade enzymes, pro-phenoloxidase (PPO), its activating enzyme (PPAE) were studied in irradiated and irradiated plus microbial challenge regimen (dual-stress) by Real-time RT-PCR (reverse-transcription-polymerase-chain-reaction). Results: An inverse correlation of radiosensitivity with developmental age of insect was observed. F1 sterility was higher than parent sterility. F1 progeny exhibited protraction in development and decreased survival upon irradiation. Sex ratio in F1 progeny was skewed towards males. PPO, PPAE, SOD and CAT transcripts were downregulated upon neonate irradiation resulting in enhanced vulnerability of larvae to incidental microbial challenge. These transcripts were upregulated in F1 progeny of sub-sterilized male moths (100 Gy) upon dual-stress. Conclusions: Irradiation impact on stress-indicating molecular responses in F1 progeny is correlated with its reproductive performance. These observations will permit defining regimen having pragmatic viability of 'F1 sterility technique' for pest suppression. Gamma dose of 100 Gy would ensure balance between induced sterility of males and their field competitiveness. These parameters would facilitate integration of biocontrol strategy with parabiological 'Sterile Insect Release Technique'.